2011
DOI: 10.1002/art.30350
|View full text |Cite
|
Sign up to set email alerts
|

End-stage renal disease due to lupus nephritis among children in the US, 1995-2006

Abstract: Purpose Little is known about the sociodemographic correlates of kidney transplantation and survival among U.S. children with lupus nephritis-associated ESRD. We aimed to identify predictors of listing for kidney transplantation (wait-listing), kidney transplantation, and mortality among children with lupus nephritis-associated ESRD. Methods Children aged 5–18 years with new onset lupus nephritis-associated ESRD were identified in the U.S. Renal Data System (1995–2006). We investigated demographic and clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
93
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 104 publications
(99 citation statements)
references
References 48 publications
4
93
1
1
Order By: Relevance
“…As in the study by Hiraki et al, 15 our study identified sociodemographic disparities in SLE outcomes in the form of fixed variables (race and ethnicity). Assessment of modifiable factors such as educational level of caregivers, social support, and other psychosocial factors is beyond the scope of the PHIS.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…As in the study by Hiraki et al, 15 our study identified sociodemographic disparities in SLE outcomes in the form of fixed variables (race and ethnicity). Assessment of modifiable factors such as educational level of caregivers, social support, and other psychosocial factors is beyond the scope of the PHIS.…”
Section: Discussionmentioning
confidence: 87%
“…20 In that study, which was not restricted to inpatients, $2 ICD-9 codes for glomerulonephritis, proteinuria, or renal failure each recorded .30 days apart were required for inclusion. Possible explanations for the difference include the more stringent criteria in the study by Hiraki et al 15 or the fact that the Medicaid database encompasses outpatient data as well, thus broadening the SLE population to those without severe disease (including nephritis).…”
Section: Discussionmentioning
confidence: 99%
“…lupus nephritis in the United States were less likely to undergo transplantation and more likely to die prematurely than white patients (23).…”
Section: Discussionmentioning
confidence: 99%
“…The population-based incidence of SLE-attributed ESRD has been estimated at 3-4 per million per year (2-5). Substantial disparities have been described in population incidence of SLE-attributed ESRD, by younger age (4-6), female sex (4), black race (2, 4-6), lower socioeconomic status (SES) (7, 8), reduced access to care (9), and residence in the South (4, 6). However, there is little reliable information on the incidence of ESRD among those with SLE.…”
mentioning
confidence: 99%